A Hyaluronan Synthesis Inhibitor Delays the Progression of Diabetic Kidney Disease in A Mouse Experimental Model. Issue 5 (27th May 2021) - Selman, Guillermo; Martinez, Laisel; Lightle, Andrea; Aguilar, Alejandra; Woltmann, Daniel; Xiao, Yuxuan; Vazquez-Padron, Roberto I.; Salman, Loay H.
Visual Abstract: Abstract : Key Points: Nonfasting plasma glucose positively correlates with hyaluronan levels in kidneys. Hyaluronan content in kidneys positively correlates with urine albumin-creatinine ratio. Hyaluronan synthesis inhibitor, 4-methylumbelliferone, slows the progression of diabetic kidney disease. Background: The role of hyaluronan (HA) in the development and progression of diabetic kidney disease (DKD), and the precise mechanisms and consequences of HA involvement in this pathology are still to be clarified. Methods: In this study, we assayed the effects of the HA synthesis inhibitor 4-methylumbelliferone (4-MU) on the development of DKD. Diabetic type 2 model mice (eNOS −/− C57BLKS/J db ) were fed artificial diets containing 5% 4-MU or not for 9 weeks. Plasma glucose, GFR, albumin-creatinine ratio (ACR), and biomarkers of kidney function and systemic inflammation were measured at baseline and after treatment. Diabetic nephropathy was further characterized in treated and control mice by histopathology. Results: Treated animals consumed a daily dose of approximately 6.2 g of 4-MU per kg of body weight. At the end of the experimental period, the 4-MU supplemented diet resulted in a significant decrease in nonfasting plasma glucose (516; interquartile range, 378–1170; versus 1149; interquartile range, 875.8–1287 mg/dl, P =0.05) and a trend toward lower HA kidney content (5.6±1.5 versus 8.8±3.1 ng/mg of kidney weight, P =0.07) compared with the control diet, respectively. Diabetic animals treated with 4-MU showed significantly higher GFR and lower urine ACR and plasma cystatin C levels than diabetic controls. Independent histologic assessment of DKD also demonstrated a significant decrease in mesangial expansion score and glomerular injury index in 4-MU–treated mice compared with controls. Plasma glucose showed a strong correlation with kidney HA levels ( r =0.66, P =0.01). Both total hyaluronan ( r =0.76, P =0.007) and low molecular weight hyaluronan content ( r =0.64, P =0.04) in the kidneys correlated with urine ACR in mice. Conclusions: These results show the hyaluronan synthesis inhibitor 4-MU effectively slowed the progression of DKD, and constitutes a potential new therapeutic approach to treat DKD.